آليات التمويل الإسلامي في تفعيل المؤسسات الناشئة - دراسة تطبيقية لتمويل مؤسسة ناشئة في القرض الشعبي الجزائري وكالة سوق أهراس - - نادية حواسنية; حكيمة بن عورة (My University, 2024)
This study aims to highlight the role that Islamic finance can play in supporting and developing emerging institutions, and making them a real actor in economic development, in light of the diversity of Islamic financing forms in line with the needs of these institutions. Islamic finance is based on the principle of sharing profits and losses, which is commensurate with the risk-taking nature of emerging institutions, and the compatibility of Islamic financial products provided by Islamic banks and windows in particular with the principles of Islamic Sharia, are considered a factor that attracts emerging institutions. However, through our applied study in the Islamic window of the Algerian Popular Credit Bank, we found that the available financing formulas are limited, which are limited to Murabaha directed to financing a short-term cycle in addition to Ijarah ending with ownership. This is due to the difficulty of assessing risks on the part of the bank and the weakness of the guarantees provided by those requesting financing. In light of the great demand for Islamic finance by emerging institutions, the need for financial engineering émergés in developing a comprehensive strategy to develop the Islamic financial industry in Algeria. تهدف هذه الدراسة إلى إبراز الدور الذي يمكن أن يلعبه التمويل الإسلامي في دعم و تطوير المؤسسات الناشئة، وجعلها فاعلا حقيقيا في التنمية الاقتصادية، في ظل تنوع صيغ التمويل الإسلامي بما يتوافق مع احتياجات هذه المؤسسات. فقيام التمويل الإسلامي على مبدأ المشاركة في الأرباح و الخسائر الذي يتناسب مع طبيعة المؤسسات الناشئة المخاطرة، وتماشي المنتجات المالية الإسلامية المقدمة من طرف البنوك والشبابيك الإسلامية بصفة خاصة مع مبادئ الشريعة الإسلامية، يعتبران عاملا جذب للمؤسسات الناشئة.لكن من خلال دراستنا التطبيقية بالشباك الإسلامي ببنك القرض الشعبي الجزائري تبين لنا محدودية صيغ التمويل المتاحة والتي تنحصر في المرابحة الموجهة إلى تمويل دورة قصيرة الأجل إضافة إلى الإجارة المنتهية بالتمليك،ويعود ذلك إلى صعوبة تقييم المخاطر من طرف البنك و ضعف الضمانات المقدمة من طالبي التمويل . وفي ظل الإقبال الكبير للمؤسسات الناشئة علي التمويل الإسلامي تظهر الحاجة إلى الهندسة المالية في وضع إستراتيجية شاملة لتطوير الصناعة المالية الإسلامية في الجزائر Cette étude vise à mettre en évidence le rôle que peut jouer la finance islamique pour soutenir et développer les institutions émergentes, et en faire un véritable acteur du développement économique, à la lumière de la diversité des formes de financement islamique en adéquation avec les besoins de ces institutions. La finance islamique repose sur le principe du partage des profits et des pertes, proportionné à la nature de prise de risque des institutions émergentes, et la compatibilité des produits financiers islamiques fournis par les banques et guichets islamiques, en particulier avec les principes de la charia islamique, est considérée un facteur qui attire les institutions émergentes. Cependant, à travers notre étude appliquée au guichet islamique de la Banque populaire algérienne de crédit, nous avons constaté que les formules de financement disponibles sont limitées, qui se limitent à la Murabaha orientée vers le financement d'un cycle à court terme en plus de l'Ijarah se terminant par la propriété. En raison de la difficulté d'évaluer les risques de la part de la banque et de la faiblesse des garanties fournies par les demandeurs de financement. À la lumière de la forte demande de financement islamique de la part des institutions émergentes, le besoin d’ingénierie financière apparaît dans l’élaboration d’une stratégie globale visant à développer l’industrie financière islamique en Algérie.
Keywords: Keywords: Islamic finance; emerging institutions; Islamic financing formulas; Islamic financial institutions; Islamic window; Algerian popular loan; financial engineering.; الكلمات المفتاحية: التمويل الإسلامي،المؤسسات الناشئة ،صيغ التمويل الإسلامي ،المؤسسات المالية الإسلامية،الشباك الإسلامي ،القرض الشعبي الجزائري، الهندسة المالية; Mots clés : Finance islamique; institutions émergentes; formules de financement islamique; institutions financières islamiques; guichet islamique; emprunt populaire algérien; ingénierie financière.